Discovery of Novel Caeridins from the Skin Secretion of the Australian White’s Tree Frog, Litoria caerulea - Lei Li; Qing Wu; Xi Wang; Huimin Lu; Xinping Xi; Mei Zhou; Chris J. Watson; Tianbao Chen; Lei Wang (International Journal of Genomics)
Abundant biologically active peptides have been discovered from frog skin secretions, a rich natural source of bioactive compounds with great potential in drug discovery. In this study, three Caeridin peptides, namely, Caeridin-1, S5-Caeridin-1, and Caeridin-a1, were discovered from the skin secretion of the Australian White’s tree frog, Litoria caerulea, for the first time, by means of combining transcriptomic and peptidomic analyses. It also represents the first report on bioactive Caeridins since this family of peptides was initially studied 20 years ago. Chemically synthetic versions of each natural Caeridin demonstrated promising bioactivities either on rat smooth muscles or against microbial growth. Specifically, Caeridin-1 produced contraction of rat bladder smooth muscle, while S5-Caeridin-1 induced relaxation of rat ileum smooth muscle, both at nanomolar concentrations. Moreover, Caeridin-a1 was shown to potently inhibit the growth of the planktonic Gram-positive bacteria Staphylococcus aureus (S. aureus), methicillin-resistant S. aureus (MRSA), and Enterococcus faecalis (E. faecalis), the Gram-negative bacterium, Escherichia coli (E. coli), and the yeast, Candida albicans (C. albicans). The discovery of these Caeridins may induce further intensive and systematic studies of frog skin peptides to promote the discovery of natural templates as lead compounds for drug discovery and therapeutic application.